The Role of Universities in the Competitiveness of Cities and Urban Agglomerations - A. A. Popov; P. P. Glukhov (Moscow Polytechnic University, 2020)
The article examines the problem of assessing the competitiveness of universities from the perspective of regional and urban development. The paper raises the question of taking into account the criteria aimed at examining the benefits of universities for the territory of presence in the modern methodology of assessing the effectiveness of universities. The article considers the advisability of integrating the results of international university rankings in the development of indices which assess the impact of universities on urban development. It includes a review of the methodologies of compiling international city rankings (Global Cities Index, Cities of opportunity, Mercer Quality of Living, The Global City Competitiveness Index, QS Best Student Cities) in order to identify the content and significance of the criteria aimed at assessment of the effectiveness of universities. The paper gives a critical assessment of international university rankings (Qs World University Rankings, Times Higher Education, Academic Ranking of World Universities). It also proposes criteria to evaluate universities from the perspective of the benefits they bring to the cities in which they are present. The article was prepared as part of the research work of the state task of the RANEPA under the President of the Russian Federation.